(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article is devoted to the psycholinguistic study of the concept of linguistic consciousness, the formation of psycholinguistics as an object, its founders, the results of the analysis of concepts and units uniting around linguistic consciousness in the field of psycholinguistics and linguistics.